Therapeutic pediatric nutrition - Sharma, Madhu Dietician (Jaypee, 2011)
The book "Therapeutic Pediatric Nutrition" elucidates the dietetic management of common as well as uncommon diseases of childhood. Each chapter in this book gives complete information in every aspect of therapeutic dietetics and covers background, pathogenesis of factors leading to nutritional disorders, nutritional requirements in the particular disease entity and also dietary management. This book also entails the menu planning and development of recipes of all disorders in detail. The book has 21 chapters. The dietary management and nutrition support of several disorders such as diabetes mellitus, kidney disorders, celiac disease and enteral feeding are explained in detail. Rare disorders like inborn errors of metabolism are also covered in this book. Numerous tables in the text summarize the important recommendations. This book is found to be a useful guide for all trainers involved in the teaching of nutrition in colleges and other health care institutions.